“Exile from Ireland Left Him a Stranger Everywhere“: Representation of Dublin in Selected Louis Macneice’s Poetry and Some of the Stories from James Joyce’s Dubliners” - Czernecka, Gabriela (Studia Celtica Posnaniensia, 2020)
This paper discusses the representation of Dublin in the selected poetry of Louis MacNeice and some of the stories from James Joyce’s collection Dubliners. A close investigation of the city as a representative of urban space is interlinked with an examination of its role from the perspective of psychogeography. Both techniques are applied to show why and how two Irish authors portray the multi-dimensional decay of life in the city. In order to paint a whole picture of the relation between ‘space’ and ‘human’, I will also review the biographies of MacNeice and Joyce. For MacNeice, who was tormented by the experiences of domestic Belfast, going to the South was a promising escape. Yet, the change of urban setting did not bring him the expected result. MacNeice quickly became aware of the dirty, paralysed face of Dublin. Similarly, the childhood and day-to-day reality of the lower-middle-class profoundly shaped Joyce’s perspective of Dublin and, eventually, prompted him to go into deliberate exile in Europe. In his writings, however, Dublin constitutes the focal point of the structure, becoming an active participant in the events. Therefore, Dublin for MacNeice and Joyce is a place characterized by blandness, powerlessness in the face of foreign influences, and suffering caused by inertia.